2014
DOI: 10.5172/jfs.2014.20.1.88
|View full text |Cite
|
Sign up to set email alerts
|

Psychological health and provision of grandchild care in non-custodial ‘baby boomer’ grandparents

Abstract: Our study explored the relationships between baby boomer grandparents' mental health and the multiple roles they commonly fulfi l: Grandchild care, other family care, home duties, and paid work. There is limited research on non-custodial grandparenting. Studies to date have suggested that psychosocial distress may be more associated with satisfaction levels than with actual time spent on activities, but these studies are mainly qualitative and have not always excluded grandparents who only provide secondary gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 20 publications
2
3
1
Order By: Relevance
“…Our findings support the idea that taking care of grandchildren is good for the subjective well-being of older adults (Arpino et al, 2018; Triadó et al, 2014; Wang, 2018; Young and Alice, 2014), even though this relationship is at a very marginal level among urban samples. Generally, urban older adults with higher educational attainment are likely to have more resources and opportunities to participate in other activities (Arpino et al, 2018).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our findings support the idea that taking care of grandchildren is good for the subjective well-being of older adults (Arpino et al, 2018; Triadó et al, 2014; Wang, 2018; Young and Alice, 2014), even though this relationship is at a very marginal level among urban samples. Generally, urban older adults with higher educational attainment are likely to have more resources and opportunities to participate in other activities (Arpino et al, 2018).…”
Section: Discussionsupporting
confidence: 83%
“…For instance, in a comparative study covering 20 countries in Europe, Arpino et al (2018) found that grandparental childcare, regardless of intensity, is generally associated with higher life satisfaction. Young and Alice (2014) reached a similar conclusion about satisfaction with being grandparents. Other studies, however, have contradicted the aforementioned views on grandparenting.…”
Section: Introductionsupporting
confidence: 57%
“…Only nonsignificant results were found most likely among the studies that were not specifically focused on associations between grandparental involvement and well-being but considered a wider range of social connections or caregiving roles (i.e., caring for grandchildren was one measurement among others) (Hsu and Chang 2015 ; Nimrod 2008 ; O’Loughlin et al 2017 ; Ward et al 2019 ; Young and Denson 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…(mean time spent caring for grandchildren per week – > BDI; mean duration of daytime care & mean duration of nighttime care – > SF-12 [mental and physical component], VAS), neg. (time spent caring for grandchildren to date – > BDI, VAS; mean time spent caring for grandchildren per week – > SF-12 [both components], VAS; mean duration of daytime care – > BDI; mean duration of nighttime care – > BDI) Young and Denson ( 2014 ) Australia 148 non-custodial Australian boomer grandparents; non-representative Amount of time spent engaged in, desire to change that time, and satisfaction with four different roles: grandchild care, paid work, other family care, and home duties Psychosocial distress (symptoms of nervousness, agitation, psychological fatigue, and depression), self-esteem ns. (time spent providing care: both outcomes) Zhang et al ( 2015 ) China 3418 elderly respondents; representative Social engagement (social activity, productive activity) SRH, PWB pos.…”
Section: Appendixmentioning
confidence: 99%
“…This literature suggests that grandparents offer to undertake the responsibilities of caring for their grandchildren, devoting their remaining years to every stage of their grandchildren's growth. In this process, the elderly become happy and at peace (Song, Li, and Li 2013;Young and Denson 2014). However, our data challenges such simplistic views of grandparents' care, showing at the very least that the grandparents' "selfless dedication" is not applicable to all only child families.…”
Section: Selfless Grandparents or A Different Extent Of Individualisa...mentioning
confidence: 63%